Improvement of Determination of Trace Amount of Nitrite in Water by Primary-Secondary Wavelengths Sperctrophotometry - Gao, Hong-Wen; Zhang, Zhi-Wenn (Asian Journal of Chemistry, 2010)
In acidic solution and in the presence of p-aminobenzenesulfonic acid, the reaction between nitrite (NO2- ) and α-naphthylamine was applied for the improvement in determination of NO2- in water by primary-secondary wavelengths spectrophotometry (PSWS) which was a new analytical method to give higher precision and sensitivity than ordinary spectrophotometry. The detection limit of NO2--N was equal to 0.002 mg/L. Results showed that for the analysis of practical samples the relative standard deviations are less than 8% and the recovery rate of NO2- is between 95.0 and 107%.